Evaluasi Penerapan Contract Change Order Sebagai Solusi Permasalahan Perubahan Lingkup Kontrak - Bintang Putra Nusantara; Sutardi Sutardi (Universitas Kristen Maranatha, 2023)
Construction industry activities are increasing. Construction industry players need to be prepared to face the possibility of changes of design planed that are not in accordance with field conditions. The purpose of this research is to identify, analyze the causes and impacts of Contract Change Orders (CCO) at the pre-construction, construction implementation, and post-construction stages with case study is Proyek Simpang Susun Balaraja Timur at Tol Jakarta – Merak, Kabupaten Tangerang. The research method used is descriptive and qualitative methods by conducting Earned Value Analysis and Fishbone Analysis to identify the causal factors and impacts of CCO so that efforts can be made to mitigate the performance of the construction contract from the aspect of quality, cost, and time. The results of the analysis show 3 factors causing CCO namely consultant factors, such as lack of planning preparation and non-compliance with field conditions, project owner factors, and contractor factors. The results of Earned Value Analysis with Estimate at Completion (EAC) calculations can be used to identify the need for additional contract value and additional execution time. On initial contract identification: Cost Performance Index (CPI) is 0.77 (insufficient costs with cost overrun – Rp. 52.502,111,631.83) and Schedule Performance Index (SPI) 1.21, means that Addendum 1 needs to be done with the results: CPI is 1.17 (the costs used are sufficient from the available fees), EAC is Rp. 189,848,751,106.02 with changes in the contract value is Rp. 222,017,999,900.65, SPI is 1.21 from the initial contract value Rp. 174,437,684,167.96